PERAN MANAJEMEN SUMBERDAYA MANUSIA SEBAGAI STRATEGI KEUNGGULAN BERSAING PADA ERA KOMPETISI GLOBAL - Agung Utama (Universitas Negeri Yogyakarta, 2011)
Global competition indicated by the emerging of much competitors operate in the worldmarket and the emerging of the competitors in other countries caused business environmentbecomes dynamic and tightly competition. Pursuing competitive advantage becomes the keyfactor on winning the competition on such environment through managing the activities ofhuman resources based on strategic perspective. Based on this perspective, the strategy ofhuman resource must relevance with the business strategy. Typology of human resourcemanagement strategy is an alternative approach for formulation that strategy. Identifing theneeded role behavior of competitive strategy becoming the important factor on effectivenessof competitive strategy implementation.Key words: Global Competition, Typology of Strategy Of HRM, Competitive Strategy